2014
DOI: 10.1016/j.ophtha.2014.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Ganglion Cell Layer Thickness and Estimated Retinal Ganglion Cell Counts in the Glaucomatous Macula

Abstract: Purpose To investigate the relationship between macular ganglion cell and inner plexiform layer (mGCIPL) thickness and estimated macular retinal ganglion cell (RGC) counts in glaucoma. Design Observational cohort study. Participants A cross-sectional study of 77 healthy, 154 suspect and 159 glaucomatous eyes from the Diagnostic Innovations in Glaucoma Study (DIGS). Methods All eyes had 24-2 Standard Automated Perimetry (SAP) and optic nerve and macular imaging using high definition optical coherence tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 40 publications
5
67
2
1
Order By: Relevance
“…We found similar scores between the insulin resistant and control groups at all spatial frequencies. The preservation of CS function in insulin resistant patients may be due to mild RGC loss; considering the findings of Zhang et al, 39 it may be estimated that there was a 4% difference in the number of macular RGCs between the two groups in our study. However, it has been reported that functional visual loss occurs in cases with damage to 20% to 40% of RGCs.…”
Section: Discussionsupporting
confidence: 46%
“…We found similar scores between the insulin resistant and control groups at all spatial frequencies. The preservation of CS function in insulin resistant patients may be due to mild RGC loss; considering the findings of Zhang et al, 39 it may be estimated that there was a 4% difference in the number of macular RGCs between the two groups in our study. However, it has been reported that functional visual loss occurs in cases with damage to 20% to 40% of RGCs.…”
Section: Discussionsupporting
confidence: 46%
“…The negative correlation of mGCIPL thickness with age has been reported . mGCIPL thickness has been reported to be stable between 18 and 49 years with a progressive decrease beyond 50 years .…”
Section: Discussionmentioning
confidence: 86%
“…Macular GCIPL thickness shows a strong correlation (r 2 =0.67) with estimated macular RGC counts and, as such, currently represents one of the best imaging estimates of it 33. Thus, it would be expected to reflect central VF sensitivity better than pRNFL thickness, and accordingly, previous reports have shown stronger central (parafoveal) functional damage associations with macular GCIPL change than with pRNFL 18 34 35.…”
Section: Introductionmentioning
confidence: 91%